Management of Hepple Stage V Osteochondral Lesion of the Talus with a Platelet-Rich Plasma Scaffold. (16th March 2017) - Gu, Wenqi; Li, Tanzhu; Shi, Zhongmin; Mei, Guohua; Xue, Jianfeng; Zou, Jian; Wang, Xiaokang; Zhang, Haotong; Xu, Hongwei
Abstract : There has been no consensus on the treatment or prognosis of Hepple stage V osteochondral lesions of the talus (OLTs), especially for lesions greater than 1.5 cm 2 in size. The objective of this study was to investigate the clinical outcomes achieved upon application of a platelet-rich plasma (PRP) scaffold with a cancellous bone autograft for Hepple stage V OLTs. Fourteen patients (mean age, 39 years) were treated with a cancellous bone graft and a PRP scaffold between 2013 and 2015. The mean time to surgical treatment was 23.5 months. Ankle X-ray and magnetic resonance imaging were performed at the final follow-up. Functional outcomes were evaluated according to the Visual Analog Scale (VAS) score, American Orthopaedic Foot and Ankle Society (AOFAS) score, and Short Form 36 (SF-36) score. The range of motion (ROM) of the ankle joint and complications also were recorded. Thirteen patients completed the full follow-up, with a mean follow-up duration of 18 months. MRI demonstrated the complete regeneration of subchondral bone and cartilage in all patients. The postoperative VAS, AOFAS ankle and hindfoot, and SF-36 scores were improved significantly (all P < 0 . 0 01 ) without obvious complications. We suggest that, for the Hepple stage V OLTs, management with cancellous bone graft and PRP scaffold may be a safe and effective treatment.